2020
DOI: 10.1371/journal.pone.0232138
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of viral etiology in potentially malignant disorders and oral squamous cell carcinomas in non-smoking, non-drinking patients

Abstract: Head and neck squamous cell carcinomas (HNSCC) are the seventh most frequent cancers. Among HNSCCs, oral squamous cell carcinomas (OSCCs) include several anatomical locations of the oral cavity, but exclude the oropharynx. The known risk factors for OSCCs are mainly alcohol consumption and tobacco use for at least 75-80% of cases. In addition to these risk factors, Human papillomavirus (HPV) types 16 and 18, classified as high-risk (HR) HPV genotypes, are considered as risk factors for oropharyngeal cancers, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“… 66 Theoretically, such changes could persist after clearance of the virus. While another study detected no significant viral RNA transcripts in a set of 68 oral cancers from NSND patients, 67 this may be a fruitful avenue for investigation into mechanisms of OCSCC in NSND populations.…”
Section: Resultsmentioning
confidence: 80%
“… 66 Theoretically, such changes could persist after clearance of the virus. While another study detected no significant viral RNA transcripts in a set of 68 oral cancers from NSND patients, 67 this may be a fruitful avenue for investigation into mechanisms of OCSCC in NSND populations.…”
Section: Resultsmentioning
confidence: 80%
“…Also, Pérot et al 26 detected only HPV transcripts in one NSND case and no other oncogenic viruses in others following RNA sequencing. This study further speculated on the role of ß‐papillomaviruses and Trichomonas vaginalis virus in oral carcinogenesis which remains to be investigated 26 …”
Section: Resultsmentioning
confidence: 95%
“…This study further speculated on the role of ß-papillomaviruses and Trichomonas vaginalis virus in oral carcinogenesis which remains to be investigated. 26 Inherent cancer susceptibility among NSND patients was also investigated. Familial cancer was used as a surrogate measure of genetic predisposition and a report found that NSND patients with familial cancer history had higher odds than healthy nonsmokers and drinkers to develop OCSCC.…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is the most common and frequent type of oral cancer which accounts for approximately 90% of all oral cancers [4,5]. Annual incidence rate of oral cancer is 300,000 cases and mortality rate is 145,000 cases worldwide approximately [6]. Most common sites of OSCC occurrence are buccal mucosa, tongue and floor of the mouth [7].…”
Section: Introductionmentioning
confidence: 99%